Strength And Guarantee of Legal Certificate of Written Evidence After The Issuance of Permen ATR No. 6 Years 2018 - Mohammad Saleh; Susakti Wibowo; Reinhard Yeremia (Faculty of Law, Merdeka University Surabaya, 2022)
Research with the topic of Strength and Guarantee of Legal Certainty of Certificates as Written Evidence after the issuance of Ministerial Regulation No. ATR. 6 of 2018, referring to the principle of publicity which is used to test the strength of proof of certificates, namely strong or not strong and absolute or not absolute, there is a ambiguity between land registration based on PP. 24 of 1997 according to Article 26 paragraph (1) PP No. 24 of 1997, notification to the public for 60 (sixty) days and the principle of publicity Article 11 paragraph (1) Permen ATR No. 6 of 2018 for 14 (fourteen) working days. The matter at issue is related to the strength and guarantee of legal certainty for the certificate as written evidence. Research using the approach to legislation and a concept approach obtained a conclusion, that: The principle of publicity in PP no. 24 of 1997 for a period of 60 working days and Permen ATR No. 6 of 2018 for 14 working days, both have not guaranteed legal certainty because the publications used are negative leading to positive, where the registrant is considered the owner and other parties can still file a cancellation lawsuit as long as they can prove that the registrant registered the land in bad faith.